Wild Experiment : Feeling Science and Secularism after Darwin - Schaefer, Donovan O., 1981- (Book collections on Project MUSE., 2022)
"Wild Experiment argues that feeling and thinking are not separate. Drawing on a range of fields including science studies, philosophy, affect theory, secularism studies, psychology, and the post-critical turn in literary studies, it reconceptualizes thinking as not just connected to feeling, but defined by it. This has implications for how we understand domains often imagined to be beyond emotion, including science, secularism, and atheism. The first part of the book builds an interdisciplinary background for what Donovan O. Schaefer calls "cogency theory"-studies of how thinking is determined by feeling. The second part turns to the history of the reception of evolutionary biology to explore three case studies of scientific secularism. Reconsidering the early Darwinian controversies, the Scopes Trial, and the New Atheist movement of the 2000s, part two argues that we can't understand scientific secularism without mapping how it feels. The epilogue considers how relationships between emotion, science, and secularism shape contemporary climate denialism"--